Forest as a Therapeutic Space in Sarah Orne Jewett’s “A White Heron”: A Deep Ecological Perspective - Poudel, Uttam (Haimaprabha, 2023)
This paper seeks to analyze as to how forest has healing power in Jewett’s “A White Heron” that helps the protagonist, Sylvia, take a positive decision— not to show the nest of the white heron to the hunter, who otherwise would love to collect the birds and stuff them. This paper argues that earlier decision of Sylvia to help the hunter out by showing the nest of the beautiful white heron changes when her greater sense of involvement to the forest through the cow touches her consciousness. The root cause of this change is the therapeutic impact of the forest (Nature) to the protagonist. This study takes recourse to ecocritical stance, more particularly Barry Commoner’s four laws of ecology and Aldo Leopold’s ideas of “land community”, and “land ethics” to analyze the mentioned text as to how it advocates for biocentric world view that places emphasis on equal status of each and every organisms on this planet and hence, they must be equally treated and protected to maintain the stronghold of human-nature relationship. Aside from that, executing the idea of deep ecology, more specifically advanced by Fritjof Capra, which gives the utmost importance to the idea that humans are a part of nature but not apart and everything in the nature is interdependent and interconnected for the healthy operation of the whole system, this paper also argues that the mentioned story is a faithful literary text, which, by exhibiting the pitfalls of citified life, appeals the entire humanity to safeguard the nature to get its therapeutic effect for healthy and holistic life.